Synthesis by ATRP of Polystyrene-b-Poly(4-vinylpyridine) and Characterization by Inverse Gas Chromatography - Rajab, Mohammad; Hamieh, Tayssir; Airoudj, Aissam; Mougin, Karine; Hariri, Kamal; Rammal, Wassim; Mortada, Houssein; Akil, Mariam; Kassas, Ahmad; Toufaily, Joumana (Journal of Research Updates in Polymer Science, 2017)
A linear diblock copolymer [Polystyrene-b-Poly(4-vinyl-pyridine)] (PS-b-P4VP) was successfully prepared through Atom Transfer Radical Polymerization (ATRP). This synthesis is performed in two successive steps: using the (1-bromoethyl) benzene as initiatorand and Hexamethyl tris [2(dimethylamino)ethyl] amine as ligands in a protic solvent. The first step of the synthesis allows the realization of block polystyrene having a terminal function; however, Bromine (Br) permits the grafting of the second successive block P4VP. RMN -1H demonstrates that the P4VP block has been grafted onto the PS block. The molecular weight of PS-b-P4VP is determined by size exclusion chromatography, and its thermal stability is examined by TGA. The surface and the thermodynamic properties of this copolymer are studied by inverse gas chromatography (IGC). The new Hamieh Model shows that the synthesized copolymer PS-P4VP has an amphoteric behavior with rather very basic character that is six times stronger than acidic character (in Lewis terms), reflected the presence of acidic and basic groups in the structure of the PS-P4VP copolymer, more particularly the presence of benzenic, methyl and vinylpyridine groups.